On Existence and Uniqueness of an Integrable Solution for a Fractional Volterra Integral Equation on ð‘¹+ - Ghaffoori, Faez N. (Iraqi Journal of Science, 2020)
In this paper, by using the Banach fixed point theorem, we prove the existence and uniqueness theorem of a fractional Volterra integral equation in the space of Lebesgue integrable ð¿1(ð‘…+) on unbounded interval [0,âˆž).